2003
DOI: 10.1021/es030319u
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Personal, Indoor, and Outdoor Exposures to Hazardous Air Pollutants in Three Urban Communities

Abstract: Two-day average concentrations of 15 individual volatile organic compounds (VOCs) were measured concurrently in (a) ambient air in three urban neighborhoods, (b) air inside residences of participants, and (c) personal air near the breathing zone of 71 healthy, nonsmoking adults. The outdoor (O), indoor (I), and personal (P) samples were collected in the Minneapolis/St. Paul metropolitan area over three seasons (spring, summer, and fall) in 1999 using charcoal-based passive air samplers (3M model 3500 organic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
114
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 22 publications
13
114
3
3
Order By: Relevance
“…Previous population-based studies in the US suggest that levels of many VOCs are typically higher inside residences than matched outdoor concentrations (Wallace et al, 1985Wallace, 1991;Sexton et al, 2004). Although urban O concentrations were higher than nonurban levels, even the urban VOC levels measured in this study are relatively low compared to other large metropolitan areas in the United States (Sexton et al, 2004).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Previous population-based studies in the US suggest that levels of many VOCs are typically higher inside residences than matched outdoor concentrations (Wallace et al, 1985Wallace, 1991;Sexton et al, 2004). Although urban O concentrations were higher than nonurban levels, even the urban VOC levels measured in this study are relatively low compared to other large metropolitan areas in the United States (Sexton et al, 2004).…”
Section: Discussioncontrasting
confidence: 58%
“…P/I ratios are relatively small for the children in this study, likely because they spend a large proportion of time at home and had relatively low exposures when away from home. P/I ratios in a recent longitudinal convenience sample of adults from the Minneapolis-St Paul metropolitan area showed that, on average, P was about 30% higher than I exposures (Sexton et al, 2004). The ratio of 95th percentile to median P exposures ranged from 2.0 to 5.9 for the children in this study.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Rather than quantifying the full range of variability of personal exposure, this study aims to provide generally representative distributions of personal exposure as a comparison for exposures in restaurants/bars and stores. The total personal exposure concentrations are mostly comparable to those from studies where personal air samples were taken (Payne-Sturges et al, 2004;Sexton et al, 2004;Weisel et al, 2005;Sax et al, 2004; Table 3). Figure 4.…”
Section: Discussionsupporting
confidence: 70%
“…and poorly characterized in environmental epidemiology studies, the links between VOC exposures and environmental diseases, such as childhood asthma or leukemia, have not been well elucidated in the general population (Pappas et al, 2000;Duarte-Davidson et al, 2001;Delfino et al, 2003;Rumchev et al, 2004;Steffen et al, 2004;Knox, 2005;Elliott et al, 2006). Recent applications of passive monitors for measuring VOCs in ambient air suggest that it may be feasible to obtain personal exposure data from large numbers of subjects in future epidemiology studies of the general public Sexton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%